Lamniform shark teeth from the Late Cretaceous of southernmost South America (Santa Cruz Province, Argentina) - Schroeter, Elena R. (2014)
Here we report multiple lamniform shark teeth recovered from fluvial sediments in the (Campanian-Maastrichtian) Cerro Fortaleza Formation, Santa Cruz Province, Argentina. This small tooth assemblage is compared to various lamniform sharks possessing similar dental morphologies, including Archaeolamna, Cretalamna, Dwardius, Dallasiella, and Cretodus. Although the teeth share numerous morphological features with the genus Archaeolamna, including a developed neck that maintains a relatively consistent width along the base of the crown, the small sample size and incomplete nature of these specimens precludes definitive taxonomic assignment. Regardless, the discovery of selachian teeth unique from those previously described for the region broadens the known diversity of Late Cretaceous South American sharks. Additionally, the discovery of the teeth in fluvial sandstone may indicate a euryhaline paleobiology in the lamniform taxon or taxa represented by this tooth assemblage.